Distribución a nivel genérico de ungulados nativos de América del Sur y Antártida, durante el Cenozoico - Gelfo, Javier Nicolás; Croft, Darin; López, Guillermo M.
A remarkable diversity of plant-eating mammals known as South American native ungulates (SANUs) flourished in South America for most of the Cenozoic. Although some of these species likely filled ecological niches similar to those of modern hoofed mammals, others differed substantially from extant artiodactyls and perissodactyls in their skull and limb anatomy and probably also in their ecology. Notoungulates and litopterns were the longest-lived and most diverse SANU clades and survived into the Quaternary; astrapotheres went extinct in the late Miocene, whereas other SANU groups were restricted to the Paleogene. Neogene notoungulates were quite specialized in craniodental structure, but many were rather unspecialized postcranially; in contrast, litopterns evolved limb specializations early in their history while maintaining more conservative dentitions. In this article, we review the current understanding of SANU evolutionary relationships and paleoecology, provide an updated compilation of genus temporal ranges, and discuss possible directions for future research. Fil: Gelfo, Javier Nicolás. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Croft, Darin. Case Western Reserve University; Estados Unidos Fil: López, Guillermo M. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina